ڈاکٹر اسرا ر احمد کے اصول سیرت نگاری: “DR. ISRAR AHMED’S PRINCIPLES OF WRITING THE BIOGRAPHY OF THE PROPHET (SEERAH)” (Al-Aasar, 2026)
Among contemporary Muslim scholars, Israr Ahmed made a significant contribution to the study of the Seerah through his writings on different aspects of the life and mission of Muhammad (P.B.U.H.). In his works, Dr. Israr Ahmed proposes a structured methodological approach for studying and writing the Seerah of the Prophet. This paper explores the principles of Seerah writing articulated by Dr. Israr Ahmed in order to understand the life and mission of the Prophet Muhammad (P.B.U.H.). The study focuses on four major principles: Seerah derived from the Qur’an, Seerah through Ahadith, Seerah through Seerah writers, and Seerah through non-Muslim scholars. Furthermore, the writings of non-Muslim historians are examined and categorized into two broad groups based on their approaches to the Seerah of the Prophet Muhammad: those who present a favorable perspective and those who present a critical interpretation. By examining these four principles, the paper highlights the methodological framework suggested by Dr. Israr Ahmed for a comprehensive understanding of the Seerah.